Phenomenology And Media Lıteracy - Ayhan, Çise; Domitran, Zrinka; Radunovic, Nikola; Tavakoli, Sepehr Dadjoi (The Turkish Online Journal of Design Art and Communication, 2016)
Is phenomenology a movement or concept? Is it a research method in human science? Different approaches have been introduced with the term of phenomenology, even it has been named as movement.It is commonly understood in either of two ways: as a disciplinary field in philosophy, or as a movement. In phenomenologist's point of view, “Phenomenology is the theory of experiences in general, inclusive of all matters, whether real or intentional, given in experiences, and evidently discoverable in them" Phenomenology demands that we seek to discover the world as it is experienced by those involved in it. It is about the nature of human experience and the meaning that people attach to their experiences. The axis of phenomenology is discussion about conscious, the conscious which becomes manifest in mind without any median and prejudice. Media literacy is a gate for this conscious and maybe we can say that considering circumstances of contemporary life in third millennium and modern society that are ensuring concept of media literacy, without media literacy this conscious is distorted. In this regards, the research paper attempts to analyse the term of phenomenology and its relation to media literacy. In this regards, what is discussed in this study is as follows: ‘What is the meaning of Phenomenology’, ‘What is the position of the term?’, ‘Who are the most important researchers on this field?’, What is the usibility of the topic’, ‘To what extend has the phenomenology been used by media literacy?’
Keywords: Phenomenology; Media Literacy; Philosophy; Media; Disciplinary Field; Fenomenoloji; Görüngü Bilimi; Fenomenolojik Yöntem; Medya; Medya Okuryazarlığı